TUBERCULOSE: FATORES DE RISCO E COMORBIDADES NO MUNICÍPIO DE CAMPO GRANDE, MATO GROSSO DO SUL - CUNHA, João Pedro Arantes da; MARQUES, Ana Maria Campos; LEMOS, Rachel Carvalho; KOWALSKI, Paloma Almeida (ANAIS DO ENIC, 2022)
-